Enhancing fatigue life by ductile-transformable multicomponent B2 precipitates in a high-entropy alloy - Rui Feng (Nature Portfolio, 2021)
A fundamental understanding of fatigue-failure mechanisms is key to develop robust structural materials. Here the authors report a high entropy alloy with enhanced fatigue life by ductile transformable multicomponent B2 precipitates, as revealed by combined experimental and simulation methods.